Techno-economic analysis of the distribution system with integration of distributed generators and electric vehicles - Golla, Naresh Kumar; Dharavat, Nagaraju; Sudabattula, Suresh Kumar; Velamuri, Suresh; Kantipudi, M. V. V. Prasad; Kotb, Hossam; Shouran, Mokhtar; Alenezi, Mohammed (Frontiers in Energy Research, 2023)
Electric Vehicles (EVs) have become a feasible alternative to conventional vehicles due to their technical and environmental benefits. The rapid penetration of EVs might cause a significant impact on the Distribution system (DS) due to the adverse effects of charging the EVs and grid integration technologies. In order to compensate an additional EV load to the existing load demand on the DS, the Distributed Generators (DGs) are integrated to the grid system. Due to the stochastic nature of the DGs and EV load, the integration of DGs alone to the DS can minimize the power losses and increase the voltage level but not up to the extent which might not improve the system stability. Here the EV which is acting as a load in Grid to Vehicle (G2V) mode during charging, can act as an energy source with its bidirectional mode of operation as Vehicle to Grid (V2G) while discharging mode. V2G is a novel resource for energy storage and provision of high and low-regulation. The proposed article enables on smart charging model of EVs and estimates the off and peak load times over a period of time and allocate the charging and dis-charging based on the constraints of State of Charge (SoC), Power and intermittent load demand. A standardized IEEE 33-node DS integrated with EV charging station (EVCS) and DGs is used to reduce the losses and improve the Voltage profile of the proposed system. Simulation results are carried out for various possible cases to assess the effective utilization of V2G for stable operation of the DS. The cost benefit analysis is also determined for G2V and V2G mode of operation for a 24-hour horizon.